2023
DOI: 10.20452/pamw.16478
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking on disease activity and prognosis of ANCA-associated vasculitis: a retrospective cohort study

Abstract: or myeloperoxidase (MPO). As AAV predominantly involve small vessels (arteries, arterioles, venules, and veins), any organ of the body can be affected. These vasculitides typically involve the upper respiratory tract, lungs, and kidneys, but skin, nervous system, gastrointestinal tract, and eye may also be affected. Although INTROduCTION Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) are a group of diseases characterized by necrotizing inflammation of small vessels that leads to damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…[27] Numerous studies have confirmed the impact of smoking on cardiovascular and lung diseases, consistent with established knowledge. [28][29][30][31][32] Moreover, Patel et al [33] found that smoking constitutes an AAV-independent risk factor for patients' prognosis, correlating with heightened disease activity. Alternatively, it is plausible that cigarette smoking heightens the probability of AAV occurrence, mediated by its influence on oxidative stress and endothelial detriment.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Numerous studies have confirmed the impact of smoking on cardiovascular and lung diseases, consistent with established knowledge. [28][29][30][31][32] Moreover, Patel et al [33] found that smoking constitutes an AAV-independent risk factor for patients' prognosis, correlating with heightened disease activity. Alternatively, it is plausible that cigarette smoking heightens the probability of AAV occurrence, mediated by its influence on oxidative stress and endothelial detriment.…”
Section: Discussionmentioning
confidence: 99%